Celebrating Christmas in Bay Area - Watkins, Howard::::::::: (1981)
Front: Howard Watkins, Betty Sanders, Adam Watkins, Harry Dalva, ?; Middle: Shirley Griffenhagen, Frances Kamp, Leslie Prusia, ?, ? Christine Watkins, Bill Sanders; Back: ??Peggy Sanders, Maril Turpin, ?